Utilizing multiscale engineered biomaterials to examine TGF‐β‐mediated myofibroblastic differentiation - Simpson, Aryssa; Krissanaprasit, Abhichart; Chester, Daniel; Koehler, Cynthia; LaBean, Thomas H.; Brown, Ashley C. (Wound repair and regeneration, 2024)
Cells integrate many mechanical and chemical cues to drive cell signalling responses. Because of the complex nature and interdependency of alterations in extracellular matrix (ECM) composition, ligand density, mechanics, and cellular responses it is difficult to tease out individual and combinatorial contributions of these various factors in driving cell behavior in homeostasis and disease. Tuning of material viscous and elastic properties, and ligand densities, in combinatorial fashions would enhance our understanding of how cells process complex signals. For example, it is known that increased ECM mechanics and transforming growth factor beta (TGF‐β) receptor (TGF‐β‐R) spacing/clustering independently drive TGF‐β signalling and associated myofibroblastic differentiation. However, it remains unknown how these inputs orthogonally contribute to cellular outcomes. Here, we describe the development of a novel material platform that combines microgel thin films with controllable viscoelastic properties and DNA origami to probe how viscoelastic properties and nanoscale spacing of TGF‐β‐Rs contribute to TGF‐β signalling and myofibroblastic differentiation. We found that highly viscous materials with non‐fixed TGF‐β‐R spacing promoted increased TGF‐β signalling and myofibroblastic differentiation. This is likely due to the ability of cells to better cluster receptors on these surfaces. These results provide insight into the contribution of substrate properties and receptor localisation on downstream signalling. Future studies allow for exploration into other receptor‐mediated processes.